Occupational burnout - Tzu-Ching Sung (Archives of Community Medicine and Public Health - Peertechz Publications, 2020)
During the 1960s, the term "burnout" originated as an explanation of the effect on an individual who struggled with substance use disorder [1]. Burnout was first identified as a potential cause of attrition in various fields by Freudenberger in 1974 [2]. Since 1974, many scientific studies on this mental circumstance have been published.